2019
DOI: 10.1016/j.onehlt.2019.100108
|View full text |Cite
|
Sign up to set email alerts
|

What makes an effective One Health clinical practitioner? Opinions of Australian One Health experts

Abstract: Despite agreement that One Health practices facilitate effective management of zoonoses, the pathways to a coordinated and collaborative approach by general medical practitioners (GPs) and veterinarians are hampered by limited understanding of how this can be practically incorporated in routine clinical settings. Data collected during a Delphi survey of Australian One Health ‘experts’ was used to explore opinions and insights into desired knowledge, attitudes and practices of effective One Health clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…Heightened concern about zoonoses amongst veterinarians is likely to be propelled by a number of factors, primarily their greater knowledge of zoonoses and their epidemiology (Chaddock, 2012;Hennenfent et al, 2018;Hoff et al, 1999;John et al, 2008;Smout et al, 2017;Steele et al, 2018Steele et al, , 2019Togami et al, 2018). Many veterinarians also have personal experience with zoonoses; nearly 45% of veterinarians in a previous Australian study reported contracting a zoonotic infection (Dowd et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Heightened concern about zoonoses amongst veterinarians is likely to be propelled by a number of factors, primarily their greater knowledge of zoonoses and their epidemiology (Chaddock, 2012;Hennenfent et al, 2018;Hoff et al, 1999;John et al, 2008;Smout et al, 2017;Steele et al, 2018Steele et al, , 2019Togami et al, 2018). Many veterinarians also have personal experience with zoonoses; nearly 45% of veterinarians in a previous Australian study reported contracting a zoonotic infection (Dowd et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were comparable with other survey‐based studies in the United States (Grant & Olsen, 1999; Hennenfent et al., 2018; Hill et al., 2012; von Matthiessen et al., 2003). This is thought by many to be a consequence of differing priorities and demands of medical and veterinary school curricula (Hodgson et al., 2019; John et al., 2008; Kahn et al., 2008; Natterson‐Horowitz, 2015; Rabinowitz & Conti, 2013; Togami et al, 2018), with medical graduates receiving less training in zoonoses, epidemiology and One Health (Chaddock, 2012; Hoff et al., 1999; John et al., 2008; Smout et al., 2017; Steele et al., 2018, 2019; Togami et al, 2018). The strategic position occupied by veterinarians and GPs in recognizing and reporting sentinel disease events (Morse et al., 2012; Rabinowitz & Conti, 2013) makes it imperative that educational interventions are put in place to improve the confidence, competence and capacity of GPs in this area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations